Research on the composition changes of ginseng powder before and after fermentation and its effect on alleviating exercise fatigue - PENG Ning, CHEN Zhixian, WANG Tao, LI Chunyang, CHEN Zhao, ZHANG Yan (Zhongguo niangzao)
In order to investigate the composition changes of ginseng powder before and after fermentation and the alleviating effect of exercise fatigue, the contents changes of total saponins, rare saponins (Rg3, Rg3R, Rg5), polysaccharide, protein, amino acid and short-chain fatty acid in ginseng powder before and after fermentation were analyzed, and a mouse experimental model to verify the alleviating effect of ginseng powder on exercise fatigue was established. The results showed that the total saponins contents of ginseng powder after fermentation were increased by 44.4%, and the rare saponins Rg3, Rg3R and Rg5 contents were 86 times, 9.3 times and 120 times of ginseng powder before fermentation, respectively. The types of free amino acids increased from 16 to 20, the total contents increased from 4.04% to 5.76%, and the lactic acid contents increased from (35.89±3.59) mg/kg to (19 702.20±1 970.22) mg/kg. Compared with the model control group, fermented ginseng powder could significantly prolong the exhaustive time of mice, reduce the lactic acid contents, malondialdehyde (MDA), urea nitrogen (BUN) and creatine kinase (CK) levels in serum of mice, increase the liver glycogen contents, lactate dehydrogenase (LDH), antioxidant enzyme levels, and adenosine triphosphate (ATP) enzyme activity, which showed that it had the effect of relieving exercise fatigue to some extent.